Effect of Whole Inedible Date and Amino Acid Supplementation on Growth Performance of Ross 308 Broiler Chicks - Abudabos, Alaeldein M; Abdelrahman, Mutassim M; Suliman, Gamaleldin M; Al-Sagan, Ahmed A (Animal Review, 2015)
This work aims to assess the potential of discarded date meal (DDM) as an alternative ingredient in broiler diets. The effect of substituting 5 or 10% of corn and soybean meal (SBM) with DDM on performance, carcass characteristics, serum constituents and nutrients retention of broilers from 12 to 35 d of age was evaluated. A total of 150 chicks were randomly distributed in a factorial arrangement (3x2) into six treatments. Three levels of DDM (0, 5 and 10%) and 2 levels of AAs (normal and high) were utilized. A significant interaction was detected for BWG (P<0.01) and FCR (P<0.001). Birds which had received 0% and 5% DDM and high AAs converted feed more efficiently when compared to those which had received low AAs. When examining the main effects for FCR, both DDM and AAs showed a significant effects on FCR (P<0.01 and 0.05, respectively). Birds received 5% DDM converted feed more efficiently as compared to 0 and 10%. Also, birds received the high AAs level converted feed more efficiently as compared to the normal level. On the other hand, breast muscle yield and abdominal fat were affected by DDM and AAs (P<0.01 and 0.05, respectively). Birds on the 0% DDM had higher breast muscle yield as compared to 5 or 10% DDM. Also, high AAs increased breast yield by 1.5% as compared to normal AAs. The results revealed that birds received 5% DDM performed better than the control or 10%. Also, supplementing diets with higher AAs level improved the performance. Based on presented evidences, it is recommended to substitute 5% of corn and SBM withDDM.